2002
DOI: 10.1159/000064206
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric Drainage (Pyloroplasty) or No Drainage in Gastric Reconstruction after Esophagectomy: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background/Aim: A gastric conduit is usually used to reconstruct the foregut after esophagectomy for cancer. The gastric emptying may be impaired after this operation, so some esophageal surgeons routinely add a pyloric drainage procedure (pyloroplasty or pyloromyotomy). We performed a meta-analysis of randomized controlled trials (RCTs) to determine the effect of pyloric drainage on patient outcomes. Methods: Medline and manual searches were done (completed independently and in duplicate) to identify all publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
1
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(127 citation statements)
references
References 14 publications
2
112
1
9
Order By: Relevance
“…No patient developed complications related to gastric outlet obstruction. While a drainage procedure has been reported to improve early motility, 14,15 it increases the complexity of the procedure, creates more bile reflux, and lengthens the operation.…”
Section: Commentmentioning
confidence: 99%
“…No patient developed complications related to gastric outlet obstruction. While a drainage procedure has been reported to improve early motility, 14,15 it increases the complexity of the procedure, creates more bile reflux, and lengthens the operation.…”
Section: Commentmentioning
confidence: 99%
“…On the contrary some authors do not share this idea and moreover they report that pyloromyotomy does not have an effect on pulmonary complications, hospital stay and mortality [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The significance and value of adding a pyloroplasty or a pyloro myotomy at the end of the interposed stomach is still debated [24]. On one hand, it may facilitate gastric emptying, thus favoring a reduced exposure to reflu x.…”
Section: Pyloric Drainage Proceduresmentioning
confidence: 99%
“…Py loroplasty can lead to b ile reflu x to the cervical remnant through the gastric tube in the long term, and thereby lead to reflu x esophagitis in the cervical remnant. In fact, Urschel et al [24] reported that pyloroplasty reduces the occurrence of early postoperative gastric outlet obstruction, but it has little effect on the patient's late outcome. On the other hand, pyloroplasty may also pro mote duodenal reflu x and, in turn, facilitate the formation of the damaging reflu xate containg pancreato-biliary secretions mixed with gastric acid secretions.…”
Section: Pyloric Drainage Proceduresmentioning
confidence: 99%